2012
DOI: 10.5301/hip.2012.9103
|View full text |Cite
|
Sign up to set email alerts
|

Randomised Trial Comparing Bone Remodelling around Two Uncemented Stems Using Modified Gruen Zones

Abstract: For assessment of bone remodelling around total hip arthroplasty using dual-emission X-ray absorptiometry (DEXA), a variety of different systems to identify regions of interest (ROI) have been used, making comparisons between stem designs difficult. The Gruen zones are now widely used for this purpose. We present the results of a randomised clinical trial comparing 2 uncemented stem designs with proximal coating, using a modification of the Gruen zones to allow improved representation of the effect of the impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…As illustrated from histomorphometry analyses of retrieval specimens, BONIT-HA coating results in osseointegration over a larger part of the coated stem surface [9, 14]. The highly bioactive biomimetic BONIT-HA coating results in both more extensive bone-implant contact and bone density in periprosthetic regions of interest compared to other currently known hydroxyapatite or porous-coated stems [9, 10]. Enhanced proximal fixation combined with reduced distal bone apposition, caused by the DOTIZE surface treatment, leaves space for relative ‘micromotion’ between the stiff distal stem and the more elastic bone [25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As illustrated from histomorphometry analyses of retrieval specimens, BONIT-HA coating results in osseointegration over a larger part of the coated stem surface [9, 14]. The highly bioactive biomimetic BONIT-HA coating results in both more extensive bone-implant contact and bone density in periprosthetic regions of interest compared to other currently known hydroxyapatite or porous-coated stems [9, 10]. Enhanced proximal fixation combined with reduced distal bone apposition, caused by the DOTIZE surface treatment, leaves space for relative ‘micromotion’ between the stiff distal stem and the more elastic bone [25].…”
Section: Discussionmentioning
confidence: 99%
“…BONIT-HA is a new generation, electrochemically deposited, biomimetic hydroxyapatite (HA) coating on top of a commercially pure titanium plasma spray (TPS) layer. It is deposited by low-temperature precipitation, is thin (10–20 μm), and has a 3D surface with high porosity (60%) and pore interconnectivity [9, 10, 12, 13]. The coating is fully resorbable and is known to be substituted by bone for about 99% [14].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This can possibly be attributed to a stress-shielding phenomenon but not to a bony integration of the distal part of the implant, as the BMD would not increase in R6 if the implant would buttress distally, which can sometimes be found after THA with other conventional straight stems [6,[35][36][37]. A recent DEXA study by Ten Broeke et al [38] compared two metaphyseal coated stems and observed only a small BMD increase in R4 after two years. However, BMD increase was only up to 3 % in R6 and a strong BMD decrease was seen in R7, indicating less load distribution to the calcar.…”
Section: Discussionmentioning
confidence: 99%